Biblioteczne integracje środowiskowe = Community integration in libraries - Wojciechowski, Jacek (Zielona Góra: "Pro Libris" Wydawnictwo Wojewódzkiej i Miejskiej Biblioteki Publicznej w Zielonej Górze)
The electronisation of communication, especially information communication, forces the libraries to enrich their repertoire, including the expansion and intensification of an additional offer, especially of a social nature, which would also have integrative effects for the surrounding communities ? either strengthening or consolidating the intra-community relationships which already exist or initiating new ones. For this purpose the most useful are projects directed to the public where people visit libraries in a physical sense. It is worth emphasizing that possible remote actions bring minimal effects in this respect. Public libraries are particularly well-suited to such tasks, especially those with not very extensive territorial coverage, as their audience is sometimes ? at least partially ? connected through a common place of residence. Primary school libraries address their offer to such a group, but only in the designated age range. On the other hand, secondary school libraries and pedagogic libraries have to deal with open-minded audiences who have no internal relations. Therefore, possible con tact between users must be inspired from the beginning, based on offers and task proposals. Convergent duties are increasingly being attributed to academic libraries, but these have limited possibilities in this respect, and practically no practical experience. In addition, they must address their activities to several different categories of the audience, from which only students and (to a lesser extent) doctoral candidates undergo pro-integration activities. Independent and younger researchers basically don?t take part in such activities. Yet, the academic libraries themselves are diverse. Main libraries, faculty and inter-faculty libraries direct their offers to heterogeneous audiences, so their pro-integration efforts are modest or none. Higher chances could be attributed to institute libraries, but these have limited possibilities and resources. Therefore, postulates of this kind would be relatively most realistic with respect to campus libraries, however, they don?t exist in Poland. But there is no doubt that this area of library tasks requires attention and ? as a consequence ? as effective a performance as possible. It concerns social needs, and creates a list of obligations which could greatly support the concept of further existence of libraries.
Keywords: integracja społeczna; biblioteka; przedsięwzięcia prointegracyjne; oferta ponadusługowa bibliotek; social integration; library; pro-integration projects; non-service offer of libraries